DIFFERENCES KNOWLEDGE, ATTITUDE, AND MOTIVATION PARTICIPANTS BPJS HEALTH MOTHER POST BID TO CHOOSE CONTRACEPTIVE MKJP TOOLS IN BANYUMAS DISTRICT - Ulfah Musdalifah; Anita Widiastuti; Sumiyati Sumiyati (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2017)
Maternal has greatest mortality of reproductive age (20-35 years), this age throughs the phases of the life cycle so it needs a continuum carelife cycle. PUS data in Puskesmas 1 Baturraden of Banyumas Regency 5079, while those who participated in BPJS Health 4079.Some factors such as knowledge, attitude, and motivation affect the choice of contraception method MKJP Based on the background, researchers are interested to take the title